Soil characterization as influenced by cropping sequences under different Agro climatic zones of Jammu Region - SHARMA, M. P.; GUPTA, RAHUL; GUPTA, R.; SHARMA, K. R. (Journal of Soil and Water Conservation, 2021)
Studies on soil characteristics under different cropping sequences as influenced by agro climatic zones revealed that soils were acidic to moderate in reaction and EC values were observed in a safe limit (< 1 ds m-1) in soils of all the zones. Organic carbon and Cation Exchange Capacity showed wide variation from low to high and medium to high respectively. The available N, P and K were also in low to medium range. The overall values of available N, P, and K were higher in soils of intermediate zone followed by temperate zone whereas low values of these nutrients were observed in soils of subtropical zone. The OC, CEC and available N, P, and K were higher in surface soils in comparison to sub surface soils.